Implementasi Program Green School dalam Penguatan Karakter Peduli Lingkungan Peserta Didik - Justin Foera-era Lase; Kerisman Harefa; Dwi Elfi Notalenta Gea; Fitri Yuliani Gulo; Kristiani Zega; Rufina Zagoto; Febri Prasetia Zega; Rivaldo Sastriawan Gulo; Aldi Januari Zai; Kharisman Hulu (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
A school environment lacking greenery and vegetation can affect learning comfort and hinder the development of students' environmentally conscious character. These issues were identified at SMP Negeri 3 Sitolu Ori, which faces limitations in ecological spatial arrangement and low student participation in environmental maintenance. This community service initiative aims to create a green and pleasant school environment, foster environmental awareness, and repurpose waste materials into useful items through the implementation of a "Green School" program. The activities took place from April to June 2026, involving the entire school community. Implementation methods included preliminary observation, hands-on practice, a participatory approach, mentoring, and evaluation. The program involved collecting and cleaning used tires, painting them with distinctive Nias ornaments, filling them with soil, planting flowers, arranging the planters, and conducting regular plant maintenance. The results indicate that the Green School program was successfully executed, transforming 10 used tires into functional and aesthetic flower planters. The program succeeded in creating a greener, more pleasant, and comfortable school environment. Scientific findings demonstrate that active student involvement facilitated by a participatory, hands-on approach is effective in enhancing environmental awareness, cleanliness consciousness, the spirit of mutual cooperation (gotong royong), and a sense of responsibility, while sustainably strengthening character traits related to environmental care.